Participatory Planning in Village Spatial Development : Creating Comprehensive Spatial Planning Documents to Enhance Investment and Development Potentials - Nur, Ahmad Amri; Sandri, Dian; Ahmada, Naufal Haidar; Purbandini, Revi Aulia; Purwati, Purwati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
The purpose of this community service is to assist Sumampir Village in compiling the Village Spatial Planning (RTRD) document as a guideline for development, attracting investment, and optimizing village potential. The method used is participatory planning through focus group discussions (FGD) and field surveys, by actively involving the community in identifying priority areas and formulating spatial strategies. The service partners include village officials and community representatives, who provide data, input, and aspirations that are important for the planning process. The evaluation instruments for this activity include assessing the specificity of priority areas set out in the RTRD document, the level of community understanding and participation during the process, and the alignment of priority area plans with village potential. The data analysis technique used is a combination of quantitative and qualitative methods, with depiction as the main tool for processing and visualizing data collected during FGDs and field surveys. Spatial data analysis using GIS is used to map regional potential based on criteria such as accessibility, legality and land availability, and economic potential, supported by field validation and stakeholder input. The resulting maps, created using tools such as ArcGIS, visually illustrate the findings and provide a strong foundation for data-based decision-making in village spatial planning. The results of this service show that Sumampir Village now has a well-structured RTRD document that identifies priority areas with significant potential for development and investment. This document is aligned with local policies, visions, and collective aspirations, which serve as a strategic reference for sustainable village growth and empower local actors in spatial management.Â